Rethinking the labor process - Wardell, Mark L., 1946-; Steiger, Thomas L., 1958-; Meiksins, Peter, 1953- (SUNY series, the new inequalities., 1999)
"While paying tribute to Harry Braverman for launching the research field known as the labor process, this book neither eulogizes nor castigates his work. Rather, it takes stock of the field, showing its blend of qualitative and quantitative methodologies and revealing its diverse contributions to the sociology of work, organizations, and stratification. Both U.S. and British authors use this venue as an opportunity to rethink and reinvigorate the labor process field, yet they maintain an intellectual commitment to the spirit with which Braverman wrote his work. They focus on aspects central to the labor process perspective, including management strategies, technology, innovations in the workplace, the value of labor, and control and resistance."--Jacket